The Effect of Working Capital Management, Leverage, and Institutional Ownership on Profitability - Ihsan Trianto; Sugianto Sugianto (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2025)
This study aims to analyze the influence of working capital management, leverage, and institutional ownership on the profitability of consumer goods companies listed on the Indonesia Stock Exchange (IDX) during the 2019–2023 period, while also examining company size as a moderating variable. The consumer goods sector, which has a large market potential in Indonesia, makes it essential to understand how these financial aspects affect company performance. Working capital management plays a crucial role in maintaining liquidity and operational efficiency, leverage determines the extent to which companies rely on debt financing, and institutional ownership reflects external monitoring that can drive managerial discipline. Company size is considered a moderating factor that could strengthen or weaken these relationships, especially in influencing profitability levels. Using a quantitative approach, the research findings reveal that each of the main variables—working capital management, leverage, and institutional ownership—partially and significantly affects profitability. More specifically, company size is found to moderate the effect of leverage on profitability, indicating that larger firms may be better positioned to optimize debt usage compared to smaller firms. This study not only provides empirical evidence regarding financial determinants of profitability but also enriches the discussion on how moderating factors such as firm size can influence the dynamics of corporate financial performance. The findings are expected to provide valuable insights for stakeholders, including managers seeking to optimize financial policies, investors evaluating company performance, and academics or researchers interested in exploring further implications for corporate governance and financial strategy in emerging markets like Indonesia. In conclusion, the study highlights the importance of managing financial variables strategically to sustain profitability in the highly competitive consumer goods industry.